1990
DOI: 10.1002/app.1990.070400101
|View full text |Cite
|
Sign up to set email alerts
|

Determination of additives in biomer and lycra spandex by pyrolysis tandem mass spectrometry and time temperature resolved pyrolysis mass spectrometry

Abstract: SynopsisPyrolysis mass spectrometry (Py-MS), time/temperature resolved Py-MS (WR-Py-MS), and pyrolysis tandem m a s spectrometry (Py-MS/MS) were used to determine the structure of an additive present in Biomer and Lycra Spandex. The additive was found to form a second phase in the polymer matrix which was insoluble in N, N'-dimethylacetamide. This insoluble portion (7% by weight) was separated by centrifugation. The structure of this additive is proposed t o be poly(2-diisopropyl amino ethyl methacrylate) (DPA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The nature of interactions between commercially available PU, that contain additives and/or contaminants, with the host body is not predictable. It has been suggested that these auxiliary chemicals can migrate from the bulk of the polymer to the surface, and subsequently be discharged into the surrounding environment [ 12, [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of interactions between commercially available PU, that contain additives and/or contaminants, with the host body is not predictable. It has been suggested that these auxiliary chemicals can migrate from the bulk of the polymer to the surface, and subsequently be discharged into the surrounding environment [ 12, [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the presence of three major additives in different BiomerTM lots [7] has been reported. These additives are: a polysiloxane which may be due to 50 contamination during synthesis of polymer [8]; a high-molecular weight UV stabilizer identified as poly(diisopropylaminomethacrylate-co-decylmethacrylate) (PAM) [9]; and an antioxidant, the 4,4'-butylidene bis(6-t-butyl-m-cresol) [10] known under the commercial name Santowhite Powder (SP).…”
mentioning
confidence: 99%